McGraw-Hill's SAT subject test chemistry - Evangelist, Thomas A.; McGraw-Hill Book Company (New York : McGraw-Hill, 2012)
A review guide for the chemistry portion of the SAT, with five practice tests, review questions with answer explanations, test-taking strategies, and topic overviews.
Spine title: SAT subject test chemistry.
Young Adult.
Young Adult
Keywords: Chemistry -- Examinations, questions, etc; SAT (Educational test); SAT (Educational test) -- Study guides -- Chemistry; Universities and colleges -- Entrance examinations -- Study guides; Chemistry -- Examinations -- Study guides; Colleges and universities -- Entrance examinations -- Study guides; SAT (Educational test)